PENGARUH STRUKTUR MODAL, LIKUIDITAS DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN INDUSTRIPERBANKAN - Ridwan Hanafi Batubara (2020)
Thisxresearch is axquantitative studyxthat aimsxto determinexthe effect ofxcapital structure, liquidity andxprofitability onxfirm value. Thexstudy was conductedxon banking service sub-sectorxcompanies listed on the Indonesia Stock Exchange as a sample. Thextechnique of determining thexsample usingxthe nonptobability sampling.xThe sample of this study amounted to 31 banking companies listedxon thexIndonesia StockxExchange inx2016-2018. Dataxanalysis techniquesxused in this study are descriptivexstatistics and panelxdata regressionxanalysis withxthe help ofxMicrosoft Excelx2013 applicationxand E-viewsxversionx10. Basedxon the resultsxof thexanalysis showsxthat capitalxstructure, liquidity andxprofitability have no effect.